The impact of type of dietary protein, animal versus vegetable, in modifying cardiometabolic risk factors: A position paper from the International Lipid Expert Panel (ILEP). Issue 1 (January 2021) - Zhubi-Bakija, Fjolla; Bajraktari, Gani; Bytyçi, Ibadete; Mikhailidis, Dimitri P.; Henein, Michael Y.; Latkovskis, Gustavs; Rexhaj, Zarife; Zhubi, Esra; Banach, Maciej; ,; Alnouri, Fahad; Amar, Fahma; et al.
Summary: Proteins play a crucial role in metabolism, in maintaining fluid and acid-base balance and antibody synthesis. Dietary proteins are important nutrients and are classified into: 1) animal proteins (meat, fish, poultry, eggs and dairy), and, 2) plant proteins (legumes, nuts and soy). Dietary modification is one of the most important lifestyle changes that has been shown to significantly decrease the risk of cardiovascular (CV) disease (CVD) by attenuating related risk factors. The CVD burden is reduced by optimum diet through replacement of unprocessed meat with low saturated fat, animal proteins and plant proteins. In view of the available evidence, it has become acceptable to emphasize the role of optimum nutrition to maintain arterial and CV health. Such healthy diets are thought to increase satiety, facilitate weight loss, and improve CV risk. Different studies have compared the benefits of omnivorous and vegetarian diets. Animal protein related risk has been suggested to be greater with red or processed meat over and above poultry, fish and nuts, which carry a lower risk for CVD. In contrast, others have shown no association of red meat intake with CVD. The aim of this expert opinion recommendation was to elucidate the different impact of animal vs vegetable protein on modifying cardiometabolic risk factors. Many observational and interventional studies confirmed that increasing protein intake, especially plant-based proteins and certain animal-based proteins (poultry, fish, unprocessed red meat low in saturated fats and low-fat dairy products) have a positive effect in modifying cardiometabolic risk factors. Red meat intake correlates with increased CVD risk, mainly because of its non-protein ingredients (saturated fats). However, the way red meat is cooked and preserved matters. Thus, it is recommended to substitute red meat with poultry or fish in order to lower CVD risk. Specific amino acids have favourable results in modifying major risk factors for CVD, such as hypertension. Apart from meat, other animal-source proteins, like those found in dairy products (especially whey protein) are inversely correlated to hypertension, obesity and insulin resistance.